Pengetahuan, Sikap, dan Praktik Apoteker Komunitas dalam Pemantauan Pengobatan Pasien Tuberkulosis di Provinsi dengan Prevalensi Tuberkulosis Tinggi di Indonesia - Mardhiyyah, Cut Ainul; Zuniarto, Ahmad Azrul; Ryansyah, Hardi; Amanatin, Alfitia Dwi; Antonia, Vonny; Sumari, Sumari (Faculty of Mathematic and Natural Science, Garut University, 2025)
Indonesia ranks second globally in tuberculosis (TB) cases, with West Java identified as a high-burden TB region. Community pharmacists, often the first point of patient contact, have the potential to support TB monitoring. However, their role remains underutilized and understudied. This study aimed to evaluate community pharmacists' knowledge, attitudes, and practices (KAP) in monitoring TB medication, and to examine the relationships among these variables and respondent characteristics. A cross-sectional study was conducted among 419 pharmacists across 27 districts and cities in West Java Province. Data were collected via a validated online questionnaire comprising KAP domains. Descriptive statistics, Spearman’s correlation, and Chi-Square tests were used to analyze relationships between KAP scores and demographic/professional characteristics. Community pharmacists demonstrated moderate knowledge in TB treatment (14.94 ± 1.99), generally have a positive attitude towards the importance of their role and ability to monitor use of TB drug (21.6 ± 3.3). In practice, community pharmacists are low in reporting, monitoring, and providing assistance related to TB patients (10.7 ± 5.2). Significant but low correlations were observed between knowledge and attitude (r = 0.110, p = 0.024), knowledge and practice (r = 0.116, p = 0.018), and attitude and practice (r = 0.343, p < 0.001). Practice scores were significantly associated with access to patient consultation services (p < 0.001), while knowledge was linked to pharmacy location (p = 0.032), and attitude to gender (p = 0.026). Although community pharmacists in West Java show sufficient knowledge and positive attitudes, their involvement in TB monitoring practices remains limited. Targeted education and policy interventions are essential for their engagement in national TB control efforts.